Climate Insights, Issue 13, 8 July 2025 - Jeanneau, Louise; Koren, Judith; Mukherji, Aditi (CGIAR Science Program on Climate Action, 2025)
Welcome to Issue #13 of Climate Insights 2025, CGIAR’s fortnightly roundup of the latest publications on climate change impacts and adaptation, mitigation measures, and the physical science from the literature. We’re tracking trending topics in the climate space and linking them to our work for a food secure future with a brief comment on the implications of this new research on our own portfolio of climate research for development.